2019
DOI: 10.1177/1476127019864673
|View full text |Cite
|
Sign up to set email alerts
|

Becoming through doing: How experimental spaces enable organizational identity work

Abstract: This qualitative study of a magazine publishing incumbent shows how organizational identity work can be triggered when organizational members engage in business model experimentation within the bounded social setting of experimental space. The study adds to the understanding of the strategy-identity nexus by expanding on the view of business models as cognitive tools to business models as tools for becoming and by understanding the role of experimental spaces as holding environments for organizational identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 67 publications
(157 reference statements)
1
29
0
1
Order By: Relevance
“…Finally, business model experimentation is addressed as an important concept in mainstream business literature [31][32][33]. Business model innovation requires significant trial and error and ongoing business model adaptation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, business model experimentation is addressed as an important concept in mainstream business literature [31][32][33]. Business model innovation requires significant trial and error and ongoing business model adaptation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further research could enhance organizational boundary thinking by inquiring the typical boundary indicators and boundary reconfigurations in specific contexts and for specific actors, advancing recent research [ 23 25 , 72 ]. This research would enable further customization per strategic application [ 66 ] and per type of boundary work, such as identity work [ 46 ], or power work [ 39 , 47 , 61 ], but also enable a more independent use of the boundary tool by practitioners. A potential theoretical avenue that helps to navigate tensions in SBMI is the field of paradox theory, which focuses on the accommodation of interrelated and conflicting economic, environmental and social concerns involved in achieving business contributions to sustainable development [ 73 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The power boundary is typically reconfigured by a focus on network competitiveness and long-term contracts with a large element of trust instead of individual power accumulation and transactional relationships [ 45 ]. The boundary of competence typically shifts towards inclusion of repair and remanufacture skills, circular design, modular processing, but also more intangible aspects such as network collaboration, dynamic capabilities [ 46 , 47 ] and experimentation capabilities [ 44 , 48 , 49 ]. On the efficiency boundary, SBMI promotes a shift in the division of roles and activities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, our findings indicated that collective identity change occurs through a split between the practiced and idealised identity with the split being fuelled by the nature of both digital innovation and work, the desire to protect the core values and the need to survive as economic actors. In particular, we emphasise the role played by collaborative experiments as enablers of the routinised introduction of novelty and changes to the collective identity, which is similar to internal organisational processes (Bojovic et al, 2020;Garud & Karunakaran, 2018). Future studies could conduct more explicit investigations of the possibly expanding gap between ideals and practice that our emphasis on collective identity indicated.…”
Section: Digital Transformation Of Industriesmentioning
confidence: 94%
“…For example, digital technologies provide early-stage opportunities because the costs associated with experimenting in the digital realm are lower than those associated with other settings, while companies working with digital technologies have a lower threshold for engaging in innovation (Garud & Karunakaran, 2018;Nambisan et al, 2019;Yoo et al, 2012). This can lead to experiments with business models and digital innovation (Andries et al, 2013;Appio et al, 2021;Bianchi et al, 2020;Bojovic et al, 2020;Bourreau et al, 2012;Cozzolino et al, 2018;Hampel et al, 2020;Restivo & Cardoso, 2020), including the digital substitution of key products and services (Bogers et al, 2015).…”
Section: Digital Transformation Of Industries and Public Valuesmentioning
confidence: 99%